2009
DOI: 10.1016/j.jjcc.2008.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin reduces myocardial infarct size via increased nitric oxide production in normocholesterolemic rabbits

Abstract: Pre-ischemic treatment with simvastatin reduces MI size via NO production. Simvastatin could be a useful drug for coronary artery disease patients without dyslipidemia as it has direct protective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Our findings revealed that the levels of EPC, SDF‐1α, VEGF, and NO were decreased greatly in the elderly patients with multivessel reocclusions compared to the elderly patients with one‐ or two‐vessel reocclusions. Oxidative stress responses and inflammatory responses decreased the overexpressions of EPC, SDF‐1α, VEGF, and NO, and the reduced circulating EPC, SDF‐1α, VEGF, and NO led to coronary in‐stent restenosis . The present study suggested that the decreased levels of EPC, SDF‐1α, VEGF, and NO were related to coronary in‐stent reocclusion and severity of reocclusion after coronary stenting and may be considered as the important targets for treatment in a new stent design for interventional therapy of coronary artery stenoses.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Our findings revealed that the levels of EPC, SDF‐1α, VEGF, and NO were decreased greatly in the elderly patients with multivessel reocclusions compared to the elderly patients with one‐ or two‐vessel reocclusions. Oxidative stress responses and inflammatory responses decreased the overexpressions of EPC, SDF‐1α, VEGF, and NO, and the reduced circulating EPC, SDF‐1α, VEGF, and NO led to coronary in‐stent restenosis . The present study suggested that the decreased levels of EPC, SDF‐1α, VEGF, and NO were related to coronary in‐stent reocclusion and severity of reocclusion after coronary stenting and may be considered as the important targets for treatment in a new stent design for interventional therapy of coronary artery stenoses.…”
Section: Discussionmentioning
confidence: 51%
“…The oxidative stress also was associated with the production and activities of NO. Oxidative stress was inhibited by increasing NO levels, and the elevated NO levels remarkably decreased infarct size of myocardium …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, simvastatin decreases severity of injury from an induced myocardial infarction (Bao et al. ) and improves postischemic ventricular function (Lefer et al. ).…”
Section: Introductionmentioning
confidence: 99%